Základní aspekty při hodnocení značky podniku - Horváth, Martin (Vysoké učení technické v Brně. Fakulta stavební, 2020)
Táto bakalárska práca sa zaoberá problematikou metód ocenenia Goodwill stavebného podniku. Popisuje správanie zákazníkov na stavebnom trhu, navrhuje zlepšenia marketingovej komunikácie pre vybranú spoločnosť a hodnotí metódy používané pre stanovenie Goodwill firmy. Slúži k pochopeniu potreby marketingových stratégii manažmentom firiem pre udržanie konkurencie schopnosti.

This bachelor thesis main focus area is the method of evaluating the construction company Goodwill. It describes the behaviour of customers in the construction market, suggests improvements in marketing communication for the selected company and evaluates the methods used to determine the goodwill of the company. It is used to understand the needs of marketing strategies by company management to maintain competition.
Basic aspects of the brand evaluation
Keywords: Marketing; marketing v staviteľstve; marketingové stratégie; marketingová komunikácia; sociálne siete; Goodwill; Marketing; marketing in civil engineering; marketing strategy; marketing communication; social network; Goodwill